Physicochemical characterization of metal organic framework materials: A mini review - Hussein Rasool Abid; Muhammad Rizwan Azhar; Stefan Iglauer; Zana Hassan Rada; Ahmed Al-Yaseri; Alireza Keshavarz (Heliyon, 2024)
Metal-organic frameworks (MOFs) are promising materials offering exceptional performance across a myriad of applications, attributable to their remarkable physicochemical properties such as regular porosity, crystalline structure, and tailored functional groups. Despite their potential, there is a lack of dedicated reviews that focus on key physicochemical characterizations of MOFs for the beginners and new researchers in the field. This review is written based on our expertise in the synthesis and characterization of MOFs, specifically to provide a right direction for the researcher who is a beginner in this area. In this way, experimental errors can be reduced, and wastage of time and chemicals can be avoided when new researchers conduct a study. In this article, this topic is critically analyzed, and findings and conclusions are presented. We reviewed three well-known XRD techniques, including PXRD, single crystal XRD, and SAXS, which were used for XRD analysis depending on the crystal size and the quality of crystal morphology. The TGA profile was an effective factor for evaluating the quality of the activation process and for ensuring the successful investigation for other characterizations. The BET and pore size were significantly affected by the activation process and selective benzene chain cross-linkers. FTIR is a prominent method that is used to investigate the functional groups on pore surfaces, and this method is successfully used to evaluate the activation process, characterize functionalized MOFs, and estimate their applications. The most significant methods of characterization include the X-ray diffraction, which is utilized for structural identification, and thermogravimetric analysis (TGA), which is used for exploring thermal decomposition. It is important to note that the thermal stability of MOFs is influenced by two main factors: the metal-ligand interaction and the type of functional groups attached to the organic ligand. The textural properties of the MOFs, on the other hand, can be scrutinized through nitrogen adsorption-desorption isotherms experiments at 77 K. However, for smaller pore size, the Argon adsorption-desorption isotherm at 87.3 K is preferred. Furthermore, the CO2 adsorption isotherm at 273 K can be used to measure ultra-micropore sizes and sizes lower than these, which cannot be measured by using the N2 adsorption-desorption isotherm at 77 K. The highest BET was observed in high-valence MOFs that are constructed based on the metal-oxo cluster, which has an excellent ability to control their textural properties. It was found that the synthesis procedure (including the choice of solvent, cross-linker, secondary metal, surface functional groups, and temperature), activation method, and pressure significantly impact the surface area of the MOF and, by extension, its structural integrity. Additionally, Fourier-transform infrared spectroscopy plays a crucial role in identifying active MOF functional groups. Understanding these physicochemical properties and utilizing relevant characterization techniques will enable more precise MOF selection for specific applications.